Non Traumatic Painful Stiff shoulder in a Child: Outcome of Physical Management - Hasan, Suzon Al; Jafor, MA; Salauddin, AKM; Islam, MT; Ahmed, SMS; Islam, MN (TAJ: Journal of Teachers Association, 2009)
Non-traumatic painful stiff shoulder is uncommon in children. It causes morbidity in which a wide range of activity is curtailed. Patients are getting usual treatment, like other diseases without necessary advice for physical therapy. Proper management along with physical therapy will reduce the morbidity. Uncommon presentation of stiff shoulder and its management by physical therapy leads us to report the case. doi: 10.3329/taj.v15i2.3917 TAJ December 2002; Vol.15(2): 90-92